﻿Maslahah as a source of Islamic transactions (Mu'amalat) Maslahah sebagai sumber transaksi Islam (Mu'amalat) - Nik Abdul Rahim Nik Abdul Ghani,; Hayatullah Laluddin,; Amir Husin Mat Nor, (Penerbit Universiti Kebangsaan Malaysia, 2011)

(untitled)
﻿ljtihad is an important task, and the ability of undertaking it constitutes the main objective of the science of the principles of islamic jurisprudence (ilm usul al-fiqh). Beside the principles of jurisprudence, legal maxims(qawa'id fiqhiyvah) and purposes of the law (maqasidal-al shari'ah) 1ay at the core of its structure. In fact. Islamic law is synonyous with term maslahah, for: if aims at its attainment and the removal of its opposite harm (mafsadah). Recently. maslahah has emerged as an important source of the law and its capacity as such has been acknowledged by many scholars. This is particularly true in the areas of transactions and finance. Therefore, this paper attempts to examine the status of maslahah as a source of law in Islamic legal framework anddeliberate on its conditions and criterion dawabit necessary for such consideration. A few instances of its application in the area of muamalat (Islamic transactions) are presented to highlight its significance in such capaciiy